68Ga-PSMA PET/CT compared with MRI/CT and diffusion-weighted MRI for primary lymph node staging prior to definitive radiotherapy in prostate cancer: a prospective diagnostic test accuracy study - Petersen, Lars; Haberkorn, Uwe (World journal of urology, 2020)
The aim was to compare the diagnostic accuracy of 68Ga-PSMA PET/CT with conventional cross-sectional imaging and diffusion-weighted MRI (DW-MRI) for detecting lymph node metastasis (LNM) to stage prostate cancer patients. Twenty consecutive, newly- diagnosed prostate cancer patients were prospectively enrolled and underwent 68Ga-PSMA-11 PET/CT, anatomical MRI or contrast-enhanced CT, and DW-MRI prior to laparoscopic, template-based, extended lymph node dissection. Histopathological findings served as the reference test.